Legazpi City’s Willingness to Pay for Climate Induced Disaster EWS Improvements - Baria, Richelle Rhea (International Journal of Architecture and Urbanism, 2026)
Climate-induced disaster is at the center of scholarly investigation due to its increasing unpredictability and intensity, time-critical nature, and the economic losses and trauma associated with it. While there are a few studies that link willingness-to-pay (WTP) on early warning systems (EWS) for climate-induced disaster resilience, which is an example of socio-technological infrastructure, research on micro-level data WTP is still limited. Furthermore, housing conditions, which are critical in resilience discourse within the architecture and urban design fields, are not well documented for WTP analysis. While international counterparts have identified specific WTP amounts for yearly schemes, the cities in the Philippines, considered as a hotspot for climate-induced disaster, have no example for a context specific WTP model. This study investigates WTP for improvement to climate-induced disaster EWS. It used Legazpi City, a high-risk multi-hazard city having 20 or more yearly typhoons, coastal flooding, storm surges, and riverine flooding, as a case study, and mixed methods, a survey through purposive sampling, KIIs, and GIS modelling as tactics. Applying OLS regression, geostructural analysis and SEM path analysis, it was found that trauma, in the form of house clean-up, is the strongest predictor for EWS investment.